Memperkuat Integrasi Nasional Melalui Generasi Bangsa dan Teknologi Pada Pembelajaran Pendidikan Kewarganegaraan - Makruf Makruf; Muhammad Zidan Firmansyah; Sasmi Nelwati (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
Abstract Strengthening National Integration Through National Generation and Technology in Citizenship Education Learning National integration has been going on since ancient times until now, with continuity and rapid development. The aim of this research is to find out whether a sense of nationalism still exists in the nation's generation. The method used is data collection from relevant journals with the title "Strengthening National Integration Through National Generation and Technology in Citizenship Education Learning." The research results show that the importance of the spirit of nationalism must be strengthened in the nation's generation. Modern technology can be a medium for increasing national integration through civic education learning.